Analisis Kinerja Sosial dan Kinerja Keuangan Lembaga Keuangan Mikro (LKM) Usaha Ekonomi Desa-Simpan Pinjam (UED-SP) Badan Usaha Milik Desa (BUMDes) Mekar Jaya Desa Bukit Sembilan Kecamatan Bangkinang Kabupaten Kampar - Rahmi Puspita Sari; Rosnita '; Ahmad Rifai (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to analyze social performance and financial performance of microfinance institutions UED-SP Mekar Jaya. Market performance indicators formulated by Microfinance Information eXchange (MIX) used to analyze the social performance of financial institutions, and financial performance analyzed using 17 PEARLS ratio. Analysis  of the UED-SP MFI's social has reached the social mission and goals. The cumulative volume of loans 41.61 percent and the higher growth of loans volume the agricultural sector 42.73 percent, the poor borrowers is 45.65 percent and volume of loans increased 55.35 percent. Internal system  activity has developed in addition of the financial products and non-financial services, as well as increased staff incentives. The output and outcome UED-SP MFI’s was increasing in average annual, outreach of the woman borrowers  37.87 percent. The financial performance obtained that the protection is not achieved because it  doesnt have a provision for loan losses on loans greater than 12 month delinquent.Effective financial structure obtained  the net loans higher than range limit of ideal achivement,  ratio of members share capital in ideal, ratio of capital institutions in ideal. Asset quality in Non Perfoaming Loans (NPL)  and ratio of non-earning asset are in ideal. Return and cost operating expenses are not ideal while net loan income are ideal, ratio of income from non-earning liquid assets are not ideal. Signs of  growth with the asset growth and savings deposit has growth with in ideal ratio. Keywords: microfinance institution, social and financial performance,ued-sp